Micro-theory on knowledge transfer to foster disaster resilience: A grounded theory approach - Ahangama N; Prasanna R (Elsevier Ltd, 2021)
Although recent literature suggested that knowledge generation and dissemination in social networks influence resilience, research in knowledge transfer and social capital domains have shown a low tendency to integrate into theoretical frameworks. This paper discusses the process of building a micro-theory, which explains the dynamics of knowledge transfer in social networks of disaster responders in Sri Lanka. The proposed theory suggests the association among knowledge transfer, dimensions of social capital, and resilience in a disaster context. This study employs an interpretive case study research design, with an exploratory approach and uses grounded theory driven constant comparison method for data analysis. The transcriptions from 21 semi-structured interviews and participant observations of two disaster drill exercises used as the primary data source for the data analysis. The analysis of this study generates a coding pattern with six categories of concepts and proposes the theory of KTinSSC with the theoretical consensus from the two case studies. The proposed theory explains the knowledge transfer among responders who are focused mostly on the immediate survival and discusses the effect of knowledge transfer interactions on their normative beliefs. The study also suggests ways to attain higher levels of resilience among such survival-focused social groups.
(c) 2021 The Author/s
Keywords: Disaster; Grounded theory; Knowledge dynamics; Knowledge transfer; Resilience; Social capital